2021
DOI: 10.1055/a-1380-1888
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Agents in the Minor Alkaloid Groups of the Amaryllidaceae

Abstract: Over 600 alkaloids have to date been identified in the plant family Amaryllidaceae. These have been arranged into as many as 15 different groups based on their characteristic structural features. The vast majority of studies on the biological properties of Amaryllidaceae alkaloids have probed their anticancer potential. While most efforts have focused on the major alkaloid groups, the volume and diversity afforded by the minor alkaloid groups have promoted their usefulness as targets for cancer cell line scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
(799 reference statements)
0
4
0
Order By: Relevance
“…The results also highlight the potential synergistic effects of amaryllidaceae alkaloids with standard chemotherapeutic agents. Combination therapy with alkaloids has shown promise in enhancing the cytotoxic effects of conventional drugs, making them potential adjuvants for cancer treatment [25,26,35]. However, despite the promising findings, some studies revealed the emergence of drug resistance mechanisms in response to amaryllidaceae alkaloid treatment.…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
“…The results also highlight the potential synergistic effects of amaryllidaceae alkaloids with standard chemotherapeutic agents. Combination therapy with alkaloids has shown promise in enhancing the cytotoxic effects of conventional drugs, making them potential adjuvants for cancer treatment [25,26,35]. However, despite the promising findings, some studies revealed the emergence of drug resistance mechanisms in response to amaryllidaceae alkaloid treatment.…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%
“…In the same work the X-ray structures of two Amaryllidaceae alkaloids (AAs), lycorine (LYC) and narciclasine (NAR), were disclosed. AAs are natural compounds that can be extracted from Amaryllidaceae bulbs, which share a common chemical architecture and have been shown to inhibit cancer cell growth by halting protein synthesis [24,29,49,54]. A remarkable finding is the position of the dioxole moiety with regard to the A-site cleft.…”
Section: Drugs Binding To the 60s Lsu Peptidyl Transferase Centre A-sitementioning
confidence: 99%
“…460–370), who treated uterine tumors with a pessary prepared from narcissus oil [ 15 ]. To date, more than 600 alkaloids of 15 chemical groups exhibiting various biological activities have been isolated from the Amaryllidaceae plants [ 16 ]. Most of these alkaloids belong to the lycorane and crinane chemical groups; however, the majority of the scientists investigating these plants as a source of anticancer agents share the opinion that the isocarbostyril non-basic constituents of the Amaryllidaceae, such as narciclasine (NAR) and pancrastitatin (PANC) ( Figure 1 ), are likely to be the most important plant metabolites responsible for the anticancer properties of these plant species in folk medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these alkaloids belong to the lycorane and crinane chemical groups; however, the majority of the scientists investigating these plants as a source of anticancer agents share the opinion that the isocarbostyril non-basic constituents of the Amaryllidaceae, such as narciclasine (NAR) and pancrastitatin (PANC) ( Figure 1 ), are likely to be the most important plant metabolites responsible for the anticancer properties of these plant species in folk medicine. Indeed, isocarbostyrils NAR and PANC are nanomolar antiproliferative agents in cancer cell cultures [ 16 ]. Notably, Narcissus poeticus L., used by Hippocrates, is now known to contain some 0.12 g of NAR per kg of fresh bulbs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%